NINA'S NEUROTIC AND REALISTIC ANXIETY REPRESENT IN THE BLACK SWAN MOVIE (2010) - Adela Putri Hatyanti; Afina Murtiningrum (Jurnal Ilmiah Penelitian Mahasiswa, 2022)
Psychoanalysis is a Freudian branch of science that studies human psychology and can express the human soul. The links between psychoanalysis and literature are undeniable. The film Black Swan (2010) was chosen as the subject of the study because it contains some anxiety problems that the main character shows using Sigmund Freud’s Anxiety Theory. The purpose of this research was to examine the anxiety felt by the main character in the film Black Swan (2010). The research methodology is qualitative variables. The study reports the findings of the analysis in sentences or descriptive forms such as dialogues, monologues, and narratives, are used. Based on Sigmund Freud’s theory, this study describes two types of anxiety: neurotic and realistic anxieties as portrayed by Nina. The first is the Neurotic Anxiety that Nina, the main character, suffers from. The second is Realistic Anxiety portrayed by the main character Nina.